EFISIENSI TERMAL PRODUKSI STEAM DITINJAU DARI RASIO UDARA BAHAN BAKAR SOLAR PADA CROSS SECTION WATER TUBE BOILER - Ningsih, Aisyah Suci; Syakdani, Adi; Rusnadi, Irawan; Oktaviani, Yustika; Veronica, Febri; Anisya, Jihan Triani (Politeknik Negeri Sriwijaya, 2021)
Cross Section Double Drum Water Tube Boiler is a steam boiler that is used to convert water into steam by heating, where the heat source comes from the combustion of fuel in the furnace. It is said that the Cross Section of the Double Drum Water Tube Boiler is because the tube arrangement in the boiler is made in the opposite direction to the drum, then this time the tool is made of a slope of 65º on the tube with the aim of reducing the force of gravity so that it will speed up the evaporation process, and has two drums. The fuel used in this study uses liquid fuel, namely diesel with the air-to-fuel ratio as a changing variable, while 15 liters of fuel and 75 kg of boiler feed water are fixed variables. The ratio of air to fuel used ranges from 15.78 to 18.16 . From the results of this study, the best response to the performance of the Cross Section Double Drum Water Tube Boiler is the air-to-fuel ratio of 17.57 ,where the boiler efficiency is 61.12%, of saturated steam and 67.18 % of superheated steam with a steam temperature of 151 ℃ and 229 ℃ , the steam pressure has reached the optimum pressure of 5 bar.